PENDAMPINGAN PEMBELAJARAN MODEL PBL BERBASIS CARING COMMUNITY DALAM MATEMATIKA SUB BAHASAN PERBANDINGAN BAGI GURU MATEMATIKA SMP IBRAHIMY 1 SUKOREJO SITUBONDO - Moh. Atikurrahman; Mar’atus Sholehah (As-Sidanah, 2021)
The mentoring and training activities for junior high school teachers in the innovation of the Caring Community-based PBL learning model go through three stages, namely planning, implementation, and evaluation. At the planning stage, the process of identifying problems, making work plans (work plans), and classifying teaching practice tasks is carried out. There are 5 groups with the same target material. At the implementation stage, it consists of two stages; 1) training on caring community learning models with a student centered approach which includes group model class management techniques, learning media design. 2) mentoring the learning practices of junior high school teachers in the classroom based on the ability level group, group L, and group M. Evaluation activities are carried out at the end of the activity to make improvements to mistakes, teacher weaknesses in the process of implementing the learning model.